UPAYA MENINGKATKAN MOTIVASI KERJA DAN KREATIVITAS DALAM KEPEMIMPINAN PAUD - Siti Munfarijah (Institut Agama Islam Negeri Purwokerto, 2017)
Early Childhood Education Institutions (ECD) is an institution that tries to organize education development aimed at children from the age of three up to six and accomplished by providing stimulation of education to help the growth and the development of physical and spiritual children in order to have the readiness to enter higher education. To achieve these objectives, we need a leadership that can make early childhood institution become an institution that can develop early childhood potencies in accordance with the expectations of their parents and society. Besides, it also takes a leadership that can motivate teachers to have high creativity in order to reach successful learning quality. Teachers’ creativities need the supportof a leader by giving motivation/reward, teachers training, and opportunities for teachers to develop their talents so that early childhood education can continue growing and having quality.